Computational homogenization of liquid‐phase sintering based on a mixed variational format. Issue 2 (November 2016) - Öhman, Mikael; Larsson, Fredrik; Runesson, Kenneth
Abstract: In this paper a mixed velocity‐pressure variational formulation is adopted for the subscale modeling of sintering stemming from micropores with surface tension. The macroscopic response is obtained from variationally consistent homogenization. As to the driving force for sintering, the model framework allows for a non‐spherical sintering stress, derived via the homogenization procedure, which contrasts traditional macroscopic modeling. The proposed method can seamlessly handle the transition from macroscopically compressible to incompressible response. For the Representative Volume Elements (RVEs) the weakly periodic, Neumann, and Dirichlet type boundary conditions are established, and it is shown that the Hill‐Mandel condition is satisfied. The numerical examples show the transient behavior of a 2D unit‐cell subjected to free sintering. Effective macroscale properties pertinent to different boundary conditions are compared for a 3D microstructure. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)